P2Y12 inhibitors for the treatment of acute coronary syndrome patients undergoing percutaneous coronary intervention: current understanding and outcomes. (3rd October 2019) - Alexopoulos, Dimitrios; Varlamos, Charalampos; Mpahara, Aikaterini; Lianos, Ioannis
ABSTRACT: Introduction : Inhibition of P2Y12 platelet receptors consists a crucial target of pharmacologic treatment in acute coronary syndrome patients. Several controversial issues however still remain and these are analyzed. Areas covered : The significance of early and strong platelet inhibition in the early phase of STEMI and the role of pretreatment are discussed. Concerns regarding morphine administration are raised. The role of crushing integral tablets to expedite the onset of action of oral P2Y12 inhibitors is emphasized. New data on the intravenous cangrelor are reported. Antiplatelet therapies as adjunct to thrombolysis, as well as the role of de-escalation antiplatelet therapy are analyzed. Expert opinion : Pharmacodynamic studies convincingly demonstrate a gap in the onset of antiplatelet action in STEMI cases, even when prasugrel or ticagrelor loading dose is used. The clinical benefit, however, of the early platelet inhibition and pretreatment is not entirely clear. Morphine delays the onset of action of oral agents, while this is expedited by crushing the integral tablets. Cangrelor devoids of these deficiencies by achieving fast and strong platelet inhibition in all clinical scenarios. Concomitant administration of novel antiplatelet agents with thrombolysis and de-escalation of antiplatelet treatment necessitate further study to reach definite conclusion.